(untitled) (Revista Contexto & Saúde, 2025)
This study aimed to analyze the factors associated with high-risk pregnancy due to hypertension, as well as childbirth care in a high-complexity public maternity hospital linked to the Stork Network Program. This was a cross-sectional observational study conducted in a state tertiary referral maternity hospital for high-risk pregnancy and childbirth, part of the Stork Network Program, located in Fortaleza, Ceará, Brazil. A total of 300 postpartum women with high-risk deliveries participated. Most participants had low socioeconomic conditions and lived in situations of social vulnerability. Statistical associations were observed between age group and parity (p < 0.001), educational level and first pregnancy (p = 0.002), maternal age and choice of maternity hospital (p = 0.03), and age and not being admitted at the first maternity hospital visited (p = 0.014). High-risk pregnant women in socially vulnerable situations had access to prenatal care, starting in the first trimester, but faced difficulties in accessing maternity services, often going through two or more facilities in search of childbirth care. The maternity hospitals did not guarantee all the rights of pregnant women, weakening the humanization of care during childbirth and the postpartum period.